Efektivitas Media Animasi Kartun dalam Pembelajaran Menulis Teks Negosiasi pada Siswa Kelas X SMA Negeri 2 Indramayu - Ine Saadah; Nana Triana Winata; Agus Nasihin (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Writing skill, particularly in producing negotiation texts, remains a persistent challenge for tenth-grade students, who often struggle with structuring texts, limited vocabulary, and low writing motivation caused by monotonous instructional media. This study aimed to describe students' negotiation-text writing ability before and after the use of cartoon animation media and to examine its effectiveness. A quasi-experimental method with a nonequivalent control group design was employed. The sample was selected through purposive sampling, consisting of Class X-7 as the experimental group (38 students) and Class X-4 as the control group (39 students) at SMA Negeri 2 Indramayu in the 2025/2026 academic year. Data were collected through negotiation-text writing tests assessing text structure, content, and language use, complemented by observation sheets, and analyzed using the Shapiro-Wilk test, Levene's test, and the nonparametric Mann-Whitney U test with SPSS 25. Results showed that the control group's posttest mean score reached 63 (adequate category), while the experimental group achieved a mean score of 80 (good category) with a highest score of 100. The Mann-Whitney U test yielded an Asymp. Sig. (2-tailed) value of 0.000 (< 0.05), indicating a statistically significant difference between the two groups. These findings confirm that cartoon animation media effectively improves students' negotiation-text writing ability. Teachers are recommended to adopt this medium as an innovative learning strategy, and schools are encouraged to support the availability of supporting audio-visual technological facilities.